SOCIAL RESPONSIBILITY OF BUSINESS AS SUSTAINABLE DEVELOPMENT APPROACH IN MANAGEMENT - Roman Zvarych; Igor Rivilis (Agora International Journal of Economical Sciences (AIJES), 2023)
The feature of the effective functioning of social relations and the condition of sustainable dynamics of the country's development is socially responsible behaviour of business. In times of crisis, socio-economic processes become unstable, social risks increase and deepen. It is important to balance of social processes by reconciling the interests of economic entities and society, social proportions and certain priorities. In this aspect, the problem of social responsibility of business through the creation of a favourable business environment is of particular importance. As a result, it is important to study the process of corporate social responsibility as sustainable development approach in management. The objective of article is methodological research the concept of social responsibility of business, the key elements of its development, the obstacles to its implementation and systematic improvements of its management. It is proved that responsible business supports high rates of economic growth, ensuring career growth for all employees, as a growing business constantly needs to attract new employees. It is justified that the policy of social responsibility of business must be implemented at the level of strategic management in the activities of the marketing, production and sales departments, as well as in the understanding of the strategy and the readiness to implement it in the workplace. It is suggested that in order to increase the social responsibility of business, it is necessary to ensure the reliability of indicators of financial and non-financial (social) reporting and assessment of the effectiveness of socio-economic costs.
Keywords: 330